2023
DOI: 10.3390/ijms24043563
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile Reflects Stages of Fibrosis in Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a leading cause of chronic liver disease worldwide, with fibrosis stage being the main predictor for clinical outcomes. Here, we present the metabolic profile of NAFLD patients with regards to fibrosis progression. We included all consecutive new referrals for NAFLD services between 2011 and 2019. Demographic, anthropometric and clinical features and noninvasive markers of fibrosis were recorded at baseline and at follow-up. Significant and advanced fibrosis were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…Lipidomics may also be a useful tool to predict disease progression. Using the same lipidomic technique, our group has previously demonstrated that a score combining metabolic profile and lipoproteins was able to identify fast fibrosis progressors and performed better than noninvasive markers [87].…”
Section: Translational Lipidomics For Staging Nafldmentioning
confidence: 99%
“…Lipidomics may also be a useful tool to predict disease progression. Using the same lipidomic technique, our group has previously demonstrated that a score combining metabolic profile and lipoproteins was able to identify fast fibrosis progressors and performed better than noninvasive markers [87].…”
Section: Translational Lipidomics For Staging Nafldmentioning
confidence: 99%
“…This study encourages the utilization of combined PRS-HFC with non-invasive clinical fibrosis scores to identify those individuals who, being at risk of incident severe liver disease, are most at need of aggressive treatment approaches as well as intensive follow-up schedules. Fujiwara et al [50] adopted a complex study design. In short, these authors first defined the signature in their derivation set for recurrent HCC.…”
Section: Risk Stratification Of Advanced Fibrosis Cirrhosis and Hcc A...mentioning
confidence: 99%